2015
DOI: 10.1097/qai.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Obesity Contributes to Neurocognitive Impairment in HIV-Infected Patients With Increased Inflammation and Immune Activation

Abstract: Objective We tested our hypothesis that abdominal obesity when associated with increased levels of systemic and CNS immuno-inflammatory mediators contributes to neurocognitive impairment (NCI). Design Cross-sectional Setting Six Academic Centers Participants 152 patients with plasma HIV RNA <1,000copies/ml had clinical evaluations and cognitive function quantified by global deficit scores (GDS). Outcome Measures GDS, waist circumference (WC) and plasma IL-6, sCD163, and sCD14 and CSF sCD40L, sTNFrII, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 60 publications
2
65
0
2
Order By: Relevance
“…McCutchan et al, 2012, found a protective effect of increased BMI on an overall global measure of neurocognitive impairment, whereas higher waist circumference, was predictive of neurocognitive impairment after correcting for a diagnosis of AIDS or diabetes and serum triglycerides among 130 participants of the CHARTER study(McCutchan et al, 2012; Sattler et al, 2014). However, this study did not assess specific cognitive domains by BMI status.…”
Section: Discussionmentioning
confidence: 99%
“…McCutchan et al, 2012, found a protective effect of increased BMI on an overall global measure of neurocognitive impairment, whereas higher waist circumference, was predictive of neurocognitive impairment after correcting for a diagnosis of AIDS or diabetes and serum triglycerides among 130 participants of the CHARTER study(McCutchan et al, 2012; Sattler et al, 2014). However, this study did not assess specific cognitive domains by BMI status.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in WC in those more than 60 years with a leveling off of BMI suggest a concomitant loss of lean mass (an estimate of skeletal muscle) that may have important clinical consequences in an aging population: changes in WC are highly correlated with changes in trunk fat by dual-energy absorptiometry and with visceral adipose tissue area by computed tomography scan (Priya Bhagwat, et al; Measurement of Abdominal Fat Changes in HIV-Infected Individuals Initiating Therapy ; Abstract #704, presented at Conference on Retroviruses and Opportunistic Infections; Boston, MA 2/2016). Moreover, central obesity has negative metabolic effects and has been associated with increased mortality [24] and neurocognitive impairment, [25] in addition to fatty liver disease [26] and liver stiffness among HIV-infected individuals. [27] …”
Section: Discussionmentioning
confidence: 99%
“…In HIV-infected persons, poorer neurocognitive function has been associated with both increased waist circumference (a marker of visceral adiposity[85])[86] and obesity[87]. Among a subset of middle-aged, HIV-infected and at risk HIV-uninfected women in the Womens Interagency HIV Study, higher leptin levels (indicative of higher adiposity) correlated strongly with poorer neurocognitive testing performance[88].…”
Section: Consequences Of Obesity and Visceral Adipositymentioning
confidence: 99%